Case Report: First Case of Non-restrictive Ventricular Septal Defect With Congestive Heart Failure in a Chinese Han Male Infant Carrying a Class II Chromosome 17p13.3 Microduplication - Yang, Yung-Yu; Liu, Chun-Ting; Pai, Li-Fan; Hu, Chih-Fen; Chen, Shyi-Jou; Hsu, Wan-Fu (Frontiers in Pediatrics, 2022)
Chromosome 17p13.3 microduplication syndrome is considered a multisystem disorder that results in a wide variety of clinical manifestations including dysmorphic facial characteristics, brain structural malformations, developmental restriction, growth restriction, and neurocognitive disorders. The two major classes of chromosome 17p13.3 microduplication, which have different clinical presentations, are associated with specific genetic regions. Among the various known phenotypes, scattered cases with congenital heart disease (CHD) have been reported for both classes of chromosome 17p13.3 microduplication syndrome. Unfortunately, there is insufficient understanding of the correlation between chromosome anomaly induced alterations in gene expression and aberrant cardiac development, and thus early diagnosis of CHD among patients with chromosome 17p13.3 microduplication is difficult without routine prenatal cardiac assessment. One such congenital heart anomalies known to affect a substantial number of newborns worldwide isventricular septal defect (VSD), which has been found in 17p13.3 microduplication carriers, and seems to sometimes undergo spontaneous closure. We report an unprecedented case of moderate sized perimembranous-outlet VSD and congestive heart failure (CHF) in a Chinese Han male infant with a class II chromosome 17p13.3 microduplication. Despite the fact that cytogenic testing and fetal echocardiography confirmed a 249-Kb chromosome duplication within 17p13.3 that encompassed the PAFAH1B1 gene and showed the presence of VSD during prenatal period, this patient still developed a range of symptoms including sustained prolonged feeding, dyspnea, diaphoresis and retarded growth. A physical examination indicated hepatomegaly and a grade III/VI pan-systolic murmur along the left upper sternal border. Laboratory testing showed a high serum pro–B-type natriuretic peptide (pro-BNP). Imaging studies revealed cardiomegaly and a persistent VSD with related pulmonary stenosis. Since the clinical findings were compatible with CHF, we provided mainline treatment with digoxin, captopril, and furosemide, as well as fluid restriction. Despite sustained poor weight gain, the feeding behavior and the respiratory conditions of the patient improved gradually. This case report and literature review suggest that patients carrying chromosome 17p13.3 microduplication who have VSD may have an increased risk of developing CHF as young infants and hence a comprehensive cardiac evaluation is warranted to allow the early diagnosis and management of any severe heart anomalies.